East African farms: battling climate change with diversity - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East African regional program has selected six sites to test interventions that address risks related to climate change and variability. Featured here is the Lower Nyando, Kenya site. Photo: K. Trautmann Please credit accordingly.